Electrochemical Evaluation on Apical Leakage of AH26 Sealer after Smear Layer Removal - Khedmat, Seddigheh; Rezaefar, Mostafa (Iranian Endodontic Journal, 2008)
INTRODUCTION: Recently, attention has been drawn to the influence of smear layer removal on apical seal, and the relation of root canal filling material with canal wall surface in the presence and absence of the smear layer. The purpose of this study was to evaluate the influence of the smear layer removal on the apical sealing ability of AH26 sealer. MATERIALS AND METHODS: Forty extracted human anterior teeth were used in this study. All teeth were decoronated at CEJ. Root canals were prepared; and before obturation, they were randomly divided into two groups (n=17): Group A in which the smear layer was left intact, and in Group B smear layer was removed. Six roots were served as controls. After obturation, microleakage was measured by the electrochemical method for 30 days with 3-day intervals. Data were then analyzed by using Mann-Whitney test. RESULTS: Based on the results of this study, in the absence of the smear layer, a highly significant decrease of apical leakage was found (P<0.001). CONCLUSION: This study showed that the removal of the smear layer can significantly improve the apical sealing ability of AH26 sealer.